2016
DOI: 10.1093/nar/gkw588
|View full text |Cite
|
Sign up to set email alerts
|

A basic domain in the histone H2B N-terminal tail is important for nucleosome assembly by FACT

Abstract: Nucleosome assembly in vivo requires assembly factors, such as histone chaperones, to bind to histones and mediate their deposition onto DNA. In yeast, the essential histone chaperone FACT (FAcilitates Chromatin Transcription) functions in nucleosome assembly and H2A–H2B deposition during transcription elongation and DNA replication. Recent studies have identified candidate histone residues that mediate FACT binding to histones, but it is not known which histone residues are important for FACT to deposit histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Recently, it has been found that acrolein, a major component of cigarette smoke and cooking fumes, reacts with histone H4 tail lysine residues to form an acrolein adduct, which inhibits lysine acetylation and therefore disrupts interactions of the tail with binding factors needed for nucleosome 41 and chromatin assembly. 89, 90 Greenberg and coworkers have shown that DNA abasic lesions react with tail lysine residues to form cross-links whose rates of formation depend on the translational setting of the lesion in the nucleosome; furthermore, they have suggested that such cross-links would impede histone tail post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been found that acrolein, a major component of cigarette smoke and cooking fumes, reacts with histone H4 tail lysine residues to form an acrolein adduct, which inhibits lysine acetylation and therefore disrupts interactions of the tail with binding factors needed for nucleosome 41 and chromatin assembly. 89, 90 Greenberg and coworkers have shown that DNA abasic lesions react with tail lysine residues to form cross-links whose rates of formation depend on the translational setting of the lesion in the nucleosome; furthermore, they have suggested that such cross-links would impede histone tail post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…23 Deletion of the H2B tail in yeast cells upregulates a large number of yeast genes and causes significant loss of histone occupancy, which may cause partially assembled nucleosomes to be unstable; these observations revealed the essential role of this tail in repressing transcription 23, 38 and in nucleosome assembly. 39, 41 The key role of the H2B tail in regulating transcription is also shown in a study with human HeLa cells, which found that when the H2B tail is in its unacetylated state, Lys20 binds tumor suppressor P14ARF and thereby mediates transcription repression of cell cycle regulatory genes; this repression is lifted by tail acetylation. 40 …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Co-IP analysis was conducted as in Mao et al (2016) with some modifications, using Spt16-9xMyc or Nap1-9xMyc yeast strains. Briefly, 50 ml of yeast culture was collected, then resuspended in ice-cold co-IP lysis buffer [40 mM HEPES, pH 7.5, 0.1% Tween 20, 150-200 mM NaCl, 10% glycerol, 13 Protease Inhibitor Cocktail (Roche)].…”
Section: Co-ipmentioning
confidence: 99%
“…We next examined histone occupancy in yeast using a twoplasmid system (Hodges et al 2015;Mao et al 2016) to measure histone occupancy of lethal acidic patch mutants. We selected one essential residue from each class, charged (H2A D91) and uncharged (H2B L109), for our analysis.…”
Section: Phenotypic Characterization Of Essential Acidic Patch Residumentioning
confidence: 99%